A multi-decadal analysis of river discharge and suspended sediment load in three Texas coastal rivers in relation to hurricanes, seasonal rainfall, and ENSO - Yao, Qiang; Joshi, Sanjeev; Liu, Kam-Biu; Rodrigues, Erika; Yin, Dongxiao (Frontiers in Earth Science, 2022)
Coastal river discharge and sediment load exert major influence on the sustainability of coastal systems. Controlled by various hydroclimatic/hydrometeorological agents, they exhibit distinct trend/variability at different time scales. Coastal Texas, while being a major target for tropical cyclones over the past 6 decades, has been experiencing drought and flood cycles associated with ENSO in the long term. However, it is still unclear the temporal variability of river discharge and the associated sediment delivery over this area at different time scales, and the controlling factors behind it. In this study, a 58-year (1960-2017) dataset is compiled to analyze the influence of ENSO, seasonal rainfall distribution and hurricanes event on the river discharge and suspended sediment load of three Texas coastal rivers-the San Bernard River, the Brazos River, and the Trinity River, at annual, seasonal and event scales, respectively. In the short-term, all three rivers attained the highest average daily discharge and sediment load during Hurricane Harvey. On a seasonal scale, the precipitation regime exerts more influence on the Texas watersheds than tropical storms and hurricanes. Over a multi-decadal scale, amplified rainstorms during the El Niño phases likely play an important role in the overall discharge and sediment transport in large rivers along the northern Gulf coast. Overall, it is reasonable to conclude that the magnitude of hurricane impacts on the overall discharge and suspended sediment load is regulated by the duration and intensity of the rainfall, as well as the coupled drought-flood cycle in relation to the intensity of ENSO.